2007
DOI: 10.1002/smj.605
|View full text |Cite
|
Sign up to set email alerts
|

The role of managers' political networking and functional experience in new venture performance: Evidence from China's transition economy

Abstract: Drawing upon the resource-based view and transaction cost economics, this study aims to examine how various types of managerial resources (i.e., political networking and functional experience) can be beneficial to new ventures in a transitionIt has long been argued that new ventures experience liabilities from their newness and have a high failure rate, because they often have limited resources and their stable links to clients, supporters, and customers have not yet been established (Stinchcombe, 1965). The l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
901
4
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 849 publications
(931 citation statements)
references
References 41 publications
19
901
4
7
Order By: Relevance
“…Consistent with work on corporate political strategy proposing that firms seek present or future resources from governments, we view political legitimacy, which is associated with greater access to government resources, as a strategic resource for firms (Hillman 2005, Li and Zhang 2007, Peng and Luo 2000, Pfeffer and Salancik 1978. Furthermore, this resource may be especially important in emerging economies where weak formal institutions can lead firms to rely more on informal mechanisms (La Porta et al 1998, Peng andHeath 1996).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Consistent with work on corporate political strategy proposing that firms seek present or future resources from governments, we view political legitimacy, which is associated with greater access to government resources, as a strategic resource for firms (Hillman 2005, Li and Zhang 2007, Peng and Luo 2000, Pfeffer and Salancik 1978. Furthermore, this resource may be especially important in emerging economies where weak formal institutions can lead firms to rely more on informal mechanisms (La Porta et al 1998, Peng andHeath 1996).…”
Section: Introductionmentioning
confidence: 92%
“…For instance, Peng and Luo (2000) found that managers' interpersonal ties with government officials helped improve their firms' performance. Li and Zhang (2007) also found that new ventures in China rely on government officials to obtain information and funding that contribute to performance. Furthermore, firms with such political connections often have better access to resources critical for growth (Nee 1992).…”
Section: Government Monitoring and Substantive Csr Reportingmentioning
confidence: 99%
“…We also study the association between the earnings management behaviors and the presence of politically connected independent board members. Extant literature has established that political connections have a significant impact on firm performance all over the world (Li, Meng, Wang, & Zhou, 2008;Niessen & Ruenzi, 2010;Wu, Wu, Zhou, & Wu, 2012), and this effect is stronger in transition economies (Conyon, He, & Zhou, 2015;Li & Zhang, 2007). China as the largest developing economy entity has attracted a lot of attention in academia, and ISSN 2162-3082 2017 a number of studies have explored the earnings management behaviors of Chinese firms (C. J.…”
Section: Introductionmentioning
confidence: 99%
“…Firms have been found to more actively take non-market actions in emerging economies where market-supporting institutions are less developed (Li & Zhang, 2007 actions and focus on how a specific form of non-market actions would affect firm performance (Shaffer et al, 2000).…”
Section: Mao Liansheng Chairman and Ceo Of Yingli Green Energymentioning
confidence: 99%